Economic feasibility of solar power plants based on PV module with levelized cost analysis - Gurturk, Mert (Pergamon-Elsevier Science Ltd, 2019)
In this study, the cost analysis of solar power system, where is located in Elazig, Turkey is calculated according to levelized cost analysis method. In the economic feasibility studies carried out by the firms, many parameters such as interest rates, cost of money, detailed sunshine duration, monthly net profit-loss status in one year, cost of investment according to changing interest rates are not taken into consideration. All these parameters, which were not considered by the firms, have been calculated in this study. The payback period of investing in the solar power plant is calculated as 13 years, the payback period of it is calculated as an average of 6.6 years by the firms. The annual profit of a 1 MW solar energy plant is 89,467 US $. Present worth and annual capital cost of the solar power plant are calculated as 1,156,763 US $ and 1,181,875 $ US , respectively. The capital cost flow of the investing in solar power plant is determined as 5.628 US $/h. When the results obtained from this study are evaluated in a general framework, the high interest rates in developing countries will have a negative effect on the investments in the solar power plants. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Solar energy; Renewable energy; Economic feasibility; Forecast solar radiation; Photovoltaic